Comparison of landsat 8 satellite data and SEBAL model for estimating evapotranspiration of Caspian forests with combined Penman Monteith - ahmad abbasnezhad; Ali asghar Darvish sefat; javad Bazrafshan (مجله جنگل ایران, 2018)
Remote sensing-based methods were developed for resolving the limits of direct measurement methods for evapotranspiration. The purpose of this study was to investigate the capability of Landsat 8 satellite imagery and the SEBAL model for estimating actual instantaneous ( ) and daily ( ) evapotranspiration in the forest ecosystem. For this reason, Landsat 8 satellite imagery was utilized at four dates for the forests of the Ramsar city and after image processing and performing necessary calculations the map of NDVI, surface temperature, emissivity and albedo were prepared and all energy components at the surface of evapotranspiration including net radiation, soil heat flux, sensible heat flux and latent heat flux were estimated and amount of instantly ET,  and  were conducted as a map. Accuracy of estimated  and  were evaluated based on the three hour data from synoptic Ramsar weather station data using FAO Penman-Monteith method. Estimated average of  and  were 0.45 and 3.98 and calculated average of these parameters were 0.55 and 4.62 respectively. Results showed that the differences are relatively small and range between 8.38 and 15.17 percent in instantaneous scale and between 11.41 and 18.34 in daily scale. Mean RelativeDifference Percentage for  and  were 11.45 and 14.27, respectively reflecting high capability of the overall ability of the approach used in this study to estimate evapotranspiration. In conclusion based on results showed that used method in this study has the capability of producing evapotranspiration map in north forests of Iran in spring and summer.